PERANCANGAN DAN PENGUJIAN SISTEM MONITORING OPERASI ALAT PENGERING LADA MENGGUNAKAN TEKNOLOGI ARDUINO - Reynaldi Pratama; Nabawi Imron; Indra Feriadi; Zanu Saputra (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Pepper dryer technology often results in an unstable process that affects the drying consistency. This study aims to obtain a monitoring system for temperature, hot air velocity, and humidity of a pepper dryer using Arduino technology. The design of electrical hardware tools using